دور التنظيمات الارهابية في التأثير على هياكل بناء النظام الدولي المعاصر - الفطيسي الفطيسي, محمد بن سعيد (Université de M'sila, 2019)
تحتل الوحدات الرئيسية والثانوية في النظام الدولي مكانة الدماغ من الجسم البشري , حيث تعمل عبرها مختلف النشاطات والاعتمادات التبادلية خصوصا ما يتعلق منها بالسياسية والعلاقات الدولية ,ما يعني ان وجود اي خلل او تغيير في تلك الوحدات حدوث ارتباك وفوضى في مجمل النظام الدولي , الامر الذي سيؤدي بكل تأكيد كذلك الى حدوث مشاكل عديدة ومختلفة سواء على صعيد الامن والاستقرار الدولي , او حتى على صعيد طبيعة تفاعلات تلك الوحدات السياسية مع بعضها البعض , حيث نعلم ان تلك الوحدات ( ترتبط فيما بينها بعلاقات معينة بحيث اذا حدث تغيير ما في اي من هذه العلاقات فان بقية العلاقات تتغير تبعا لذلك ) ( ) والمتتبع لطبيعة وشكل النظام الدولي بعد احداث الحادي عشر من سبتمبر من العام 2001م يجد الكثير من التحولات والتفاعلات والانشطة الدولية الاستثنائية التي تؤكد اتجاه هياكل بناءه ووحداته التقليدية الى مسارات التغيير والتطور المتسارع , سواء عبر اضعاف وتراجع مكانة وقوة بعض وحداته الرئيسية كما هو الدول , او عبر محاولات دخول فواعل جديدة على تلك الوحدات الثانوية القائمة , كما هو حاصل مع المنظمات والجماعات الارهابية. وتعد المنظمات والجماعات الارهابية اليوم من ابرز المؤثرين في هياكل النظام الدولي المعاصر, ويؤكد هذا الامر طبيعة تلك التفاعلات والتبادلات الدولية التي تمكنت هذه التنظيمات من الولوج اليها عبر العديد من الانشطة الارهابية في مختلف انحاء العالم , يضاف الى ذلك تمكنها من الحصول على العديد من الاوراق الرابحة في حقل السياسة الدولية عبر تعاملاتها وعلاقاتها مع العديد من الدول , ولا شك ان امكانياتها المادية والمعنوية اتاحت لها كذلك من القدرة والقوة ما جعلها تتفوق في كثير من الاوقات على بقية الوحدات التقليدية التي سبقتها في تكوين بناء النظام الدولي منذ العام 1648م . ما يحتم بالضرورة اعادة النظر في حجم تأثير هذه الجماعات والتنظيمات الارهابية على مستقبل تشكيل وحدات النظام الدولي التقليدية في القرن 21 بوجه عام , وما يمكن ان يخلفه ذلك التأثير من مخاطر وانعكاسات سياسية وامنية على حقل السياسة والعلاقات الدولية بوجه خاص. Abstract :- The main and secondary units of the international system occupy the position of the brain components in the human body, through which the various activities and mutualizations in the field of politics and the field of international relations operate, which means that any imbalance or change in these units will cause confusion and chaos throughout the international system. In addition to the fact that there are many different problems, both in terms of security and international stability, or even in the nature of the interactions of those political units with each other, where we know that those units. The follow-up to the nature and form of the international system after the events of September 11, 2001 finds many transformations, interactions and exceptional international activities that confirm the direction of its traditional structures and units to the paths of rapid change and development, whether by weakening or weakening the status and strength of some of its main units, Attempts to enter new acts on these existing secondary units, as is the case with terrorist organizations and groups. The terrorist organizations and groups today are among the most influential in the structures of the modern international system. This confirms the nature of these international interactions and exchanges, which these organizations have managed to access through many terrorist activities around the world, in addition to the ability to obtain many trumps In the field of international politics through its dealings and relations with many countries, and there is no doubt that their material and moral potential also enabled them to power and strength, which made them excel at many times on the rest of the traditional units that preceded the formation of the international system since the Or 1648. What necessarily necessitates a reconsideration of the impact of these groups and terrorist organizations on the future of the formation of the units of the traditional international system in the 21st century in general, and the impact that this impact may have on political and security risks and repercussions on the field of politics and international relations in particular.
Keywords: التنظيمات النظام